1999
DOI: 10.2334/josnusd.41.177
|View full text |Cite
|
Sign up to set email alerts
|

Histological assessment of root cementum at periodontally healthy and diseased human teeth.

Abstract: Abstract:This study aimed to investigate and compare the lipid and polysaccharide content of the cemental surfaces of healthy and periodontally-involved teeth. Thirty

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
6
0
1
Order By: Relevance
“…To achieve appreciable periodontal regeneration, many studies 5,6,8,9,25,26 have supported the necessity of removing endotoxin and the smear layer of instrumentation on the root surface that is exposed in the periodontal pocket 25,26 . Chemical root conditioning of periodontitis‐affected root surfaces has been described with a number of agents of varying pH to eliminate factors that render the root surface bioincompatible for PDL associated with periodontal healing 27,28 .…”
Section: Discussionmentioning
confidence: 99%
“…To achieve appreciable periodontal regeneration, many studies 5,6,8,9,25,26 have supported the necessity of removing endotoxin and the smear layer of instrumentation on the root surface that is exposed in the periodontal pocket 25,26 . Chemical root conditioning of periodontitis‐affected root surfaces has been described with a number of agents of varying pH to eliminate factors that render the root surface bioincompatible for PDL associated with periodontal healing 27,28 .…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7][14][15][16][17][18][19]21 In most of the teeth in the current study, only cementum was affected by resorptions, with resorption reaching the dentin in just 24.53%, compared to 30% reported by Henry and Weinmann. However, authors such as Faltin et al 16 found no resorption on dentin of teeth orthodontically moved, and Ökte et al 22 observed affected cementum only in resorptions of both healthy and diseased teeth. Kurol et al 14 observed that 47.2% of resorptions in the control teeth they studied reached dentin, and 73.6% of resorptions in the teeth orthodontically moved reached dentin.…”
Section: Percentages Of Resorbed Volume By Group *Significant Differmentioning
confidence: 99%
“…Kurol et al 14 observed that 47.2% of resorptions in the control teeth they studied reached dentin, and 73.6% of resorptions in the teeth orthodontically moved reached dentin. However, authors such as Faltin et al 16 found no resorption on dentin of teeth orthodontically moved, and Ökte et al 22 observed affected cementum only in resorptions of both healthy and diseased teeth.…”
Section: Percentages Of Resorbed Volume By Group *Significant Differmentioning
confidence: 99%
“…The majority of the literature about radicular resorption in the permanent teeth relates to orthodontic cases. Studies regarding the presence of resorption in teeth with adult periodontitis are few (5, [11][12][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%